Abnormal Liver Function in Predicting COVID-19 Patients’ Prognosis - Steven; Callista (International Medical Journal Corp. Ltd, 2025)
Background: The literature reviewed demonstrates a significant correlation between liver function abnormalities and the prognosis of COVID-19 patients. Literature Review: Subsequent studies, including those by (Du et al., 2021) and (Singhai et al., 2021), documented that a significant percentage of hospitalized patients exhibited abnormal liver function tests, particularly in severe cases, thereby establishing a clear relationship between liver dysfunction and the severity of COVID-19. The implications of these findings underscore the necessity for healthcare providers to monitor liver function closely, as abnormalities can serve as prognostic indicators. The review of literature also indicates that the mechanisms underlying liver injury in COVID-19 are multifaceted. Studies have pointed to direct viral effects, systemic inflammatory responses, and drug-induced toxicity as contributing factors to liver dysfunction. The interplay between liver injury and inflammatory markers has been emphasized as a vital area for further research, with findings suggesting that elevated liver enzymes correlate with increased mortality risk. Conclusion: In conclusion, the literature consistently highlights that liver dysfunction is a significant factor in predicting the prognosis of COVID-19 patients. The prevalence of liver abnormalities, their association with disease severity, and the underlying mechanisms warrant close monitoring and management of liver health in this patient population. Clinicians are encouraged to incorporate routine liver function assessments into care strategies to optimize patient outcomes during the COVID-19 pandemic.